2019
DOI: 10.1111/1467-8551.12326
|View full text |Cite
|
Sign up to set email alerts
|

Regional Integration, Multinational Enterprise Strategy and the Impact of Country‐level Risk: The Case of the EMU

Abstract: The European Monetary Union (EMU) provides a new macro-level, institutional setting for multinational enterprises (MNEs). The authors investigate the impact of regional integration on MNE strategy by analysing Belgian firms' entry-mode choices in foreign markets, both EMU and non-EMU ones, with a focus on what impact remains of countrylevel risk. They demonstrate that regional integration has altered the impact of countrylevel institutional risk on MNE entry-mode choices inside the EMU. The conventional predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 98 publications
(192 reference statements)
0
8
0
1
Order By: Relevance
“…Received knowledge suggests that with high political risk, multinational enterprises will set up joint ventures and alliances with local partners who could mitigate such risks. This prediction is one of the cornerstones of the modern international business literature on operating mode choice (Hillemann, Verbeke, & Oh, 2019). However, a wide variety of operating restrictions imposed by host countries, such as limits to foreign ownership levels and access to local partners and resources, or the forced sharing of technological knowledge could discourage joint ventures and alliances.…”
Section: Cartels and Efficient Governancementioning
confidence: 98%
“…Received knowledge suggests that with high political risk, multinational enterprises will set up joint ventures and alliances with local partners who could mitigate such risks. This prediction is one of the cornerstones of the modern international business literature on operating mode choice (Hillemann, Verbeke, & Oh, 2019). However, a wide variety of operating restrictions imposed by host countries, such as limits to foreign ownership levels and access to local partners and resources, or the forced sharing of technological knowledge could discourage joint ventures and alliances.…”
Section: Cartels and Efficient Governancementioning
confidence: 98%
“…В ряде работ [2,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] приведены соображения о формировании стратегии развития дочерних предприятий, методические аспекты формирования и реализации подобных стратегий, а также методика экспертного определения конкурентных преимуществ, полученных дочерними предприятиями от нахождения в интегрированной структуре.…”
Section: заключениеunclassified
“…As one example of a ‘new normal,’ the introduction of the European Monetary Union (EMU) influenced how governments managed a variety of budgetary and financial decision‐making processes, and how EU‐based multinational enterprises (MNEs) addressed institutional risk within the region. Research revealed that the common prediction from international business theory that associated higher institutional risk with a preference for joint ventures over wholly owned subsidiaries (e.g., Grøgaard and Verbeke, ; Meyer et al, ; Yiu and Makino, ), was reversed (Hillemann et al, ). Given the presence of high‐quality regional institutions and a common currency, these MNEs began to perceive the usage of joint ventures in a higher‐risk country as inviting corruption from the national level and encouraging undesirable features of institutional risk being imposed on the firm’s operations.…”
Section: Conceptual Backgroundmentioning
confidence: 99%